Gestão de energia em edificações públicas: caso prefeitura de Manoel Viana - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Electricity consumption in Brazil has only increased in recent years and estimates have continued. Commercial panels, public and residential, which represent the buildings, are the main responsible for the consumption of electric energy in Brazil. In the year 2016 they were responsible for 48.1% of consumption and it is expected that up to 2026 represent 49.5%. Another characteristic of the Brazilian electrical system is that it is predominantly based on centralized generation, with large hydroelectric plants, far from the centers of consumption. The current climate crisis and high levels of electricity have motivated the search for new forms of energy generation, being a distributed generation of the most attractive. A distributed generation may be capable of self-arresting in a local place of consumption, as well as losses in transmission and distribution of energy. From now on, the new series of hydroelectric and thermoelectric plants can reduce the production of electric energy and reduce the consumption of electric energy. This work presents a case study of Manoel Viana public elections, with an energy program and a preliminary project of generation of distribution, through a photovoltaic power generating plant, to supply a demand of electricity of the public presences of the municipality of Manoel Viana.
Keywords: Engenharia elétrica; Geração distribuída de energia elétrica; Edifícios públicos; Manoel Viana; Energia - Consumo; Electrical engineering; Distributed generation of electric energy; Public buildings; Energy - Consumption; CNPQ::ENGENHARIAS